A modification of the Gale-Shapley algorithm used to assign Polish pupils to schools - Zakrzewska, Aleksandra (Studia Informatica. System and information technology, 2024)
Allocation algorithms based on rankings are utilized in various situations, such as selecting appropriate tasks for workers, scheduling doctors’ appointments, or assigning children to schools.Amodified version of the standard Gale-Shapley algorithm is introduced and employed in Poland’s secondary school recruitment process. This algorithm relies on students’ school results and their priority lists. During the recruitment process, students are assigned to a school on the basis of their performance and preference list. However, this approach disadvantages weaker students, as they are only considered towards the end of the process. Consequently, they are often assigned to schools with a lower priority on their lists or, in some cases, remain unassigned. The proposed modification aims to improve opportunities for students to plan their educational future more fairly, considering their individual achievements.